Synthesis and Characterization of BaTiO3/TiO2 Heterojunction Photocatalyst for Novel Application in Photocatalytic Degradation of TBBPA under Simulated Sunlight Irradiation. Issue 45 (1st December 2022) - Wang, Shifa; Yu, Chuan; Chen, Xiangyu; Zhang, Kening; Gao, Huajing; Yu, Xianlun; Zhao, Xinxin; Fang, Leiming; Chen, Xiping; Zhang, Jing
Abstract: The polyacrylamide gel method combined with low temperature sintering technology (PGMCLTST) have been used to synthesize the BaTiO3 /TiO2 heterojunction photocatalysts. The BaTiO3 /TiO2 heterojunction photocatalyst only contains tetragonal BaTiO3, rutile TiO2 and anatase TiO2, without any other impurities. Based on a variety of characterization, it was confirmed that a special heterojunction was formed between BaTiO3 and TiO2, and there were a large number of interface defects or oxygen defects in the samples. The BaTiO3 /10 wt % TiO2 heterojunction photocatalysts have high photocatalytic activity for the degradation of tetrabromobisphenol A (TBBPA) under simulated sunlight irradiation. The interfacial defects enhance the transfer and separation efficiency of charge carriers in BaTiO3 /TiO2 heterojunction photocatalysts. This technique provides a new idea for the application of BaTiO3 /TiO2 heterojunction photocatalysts and other heterojunction photocatalysts in the degradation of persistent organic pollutants (POPs). Abstract : The BaTiO3 /TiO2 heterojunction photocatalysts were synthesized by the polyacrylamide gel method combined with low temperature sintering technology. The BaTiO3 /10 wt % TiO2 heterojunction photocatalysts have high photocatalytic activity for the degradation of tetrabromobisphenol A (TBBPA) under simulated sunlight irradiation. The interfacial defects enhance the transfer and separation efficiency of charge carriers in BaTiO3 /TiO2 heterojunction photocatalysts. This technique provides a new idea for the application of BaTiO3 /TiO2 heterojunction photocatalysts and other heterojunction photocatalysts in the degradation of persistent organic pollutants (POPs).